#### Answer

$-3m+n$

#### Work Step by Step

The distributive property holds that $a(b+c)=ab+ac$ (for real numbers $a$, $b$, and $c$).
Therefore, $-(3m-n)=(-1\times3m)-(-1\times n)=-3m-(-n)=-3m+n$.

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

$-3m+n$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.